Pengaruh Literasi Keuangan, Perlindungan Data, dan Cybersecurity Terhadap Penggunaan Financial Technology - Widiyati, Dian; Erliana (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
This study aims to test and analyze how the influence of financial literacy, data protection and cybersecurity on the use of financial technology. The independent variables in this study are financial literacy, data protection and cybersecurity, while the dependent variable in this study is the use of financial technology. This research is a quantitative research using primary data in the form of questionnaires. The population of this study is students of the Faculty of Economics and Business, Pamulang University. The sampling technique uses convenience sampling techniques so that a research sample of 134 respondents was obtained. The analysis tool used in this study is Smart-PLS. The results of this study are that financial literacy does not affect the use of financial technology, data protection has a positive effect on the use of financial technology and cybersecurity has a positive effect on the use of financial technology.